1933 Haw. Sess. Laws 36-37, An Act Regulating the Sale, Transfer, and Possession of Firearms and Ammunition, § 3 - (:unkn) unknown (General Publisher, 1933)
Required every person residing in or doing business within the territory to register any firearm of any description or any ammunition within ten days to the chief of police of Honolulu or the county sheriff where the possessor resides. Violators shall be punished by fine of no more than two hundred and fifty dollars.
--
Keywords: REGISTRATION